The CLEO-III ring imaging Cherenkov detector - Mountain, R; Artuso, M; Ayad, R; Azfar, F; Efimov, A; Kopp, S; Majumder, G; Schuh, S; Skwarnicki, T; Stone, S; Viehhauser, G; Wang, J; et al. (1999)
The CLEO-III detector upgrade for charged particle identification is discussed. The RICH design uses solid LiF crystal radiators coupled with multi-wire chamber photon detectors, using TEA as the photosensor, and low-noise Viking readout electronics. Results from our beam test at Fermilab are presented. (C) 1999 Elsevier Science B.V. All rights reserved.